Cigarette and Adolescent Debt: A Phenomenological Study of Smoking Behavior for Junior High School Students in Blitar City, Indonesia - Katon Galih Setyawan; Kusnul Khotimah; Agung Stiawan; Muhammad Ilyas Marzuqi (Technium Social Sciences Journal, 2023)
This study tries to explain or reveal the meaning of the concept or phenomenon of experience which is based on the awareness that occurs in several individual junior high school students in terms of the act of smoking using Alfred Schutz’s phenomenological approach. From this research, the problem studied is what are the motives of junior high school students in Blitar City to smoke. The research subjects were junior high school students in Blitar City. Data collection techniques were obtained through observation, in-depth interviews using interview guidelines. The results of the analysis and findings of the data show that the motives for smoking behavior carried out by elementary school children are due to wrong association in the environment, lack of attention from parents, imitation of people admired in their environment and labeling ’bad’ children so that children become play a role based on the label. The motives for the goals to be achieved by these children include wanting to be admired by their peers, wanting to have lots of friends and as an attitude of resistance to parents who are over protective.